From Hidden Viromes to Synthetic Microbiomes: Reshaping Plant Disease and pest Dynamics in the Anthropocene era - Kamini Yadav,; Veenu Singh,; Priyansh Rahangdale,; Jaismeen Purba,; Harjinder Singh,; Gurvinder Singh,; P. Kalaiselvi,; Ritik Raj, (Public Health, 2026)
The hidden diversity of viruses (the “virome”) in plant and soil ecosystems is being uncovered by metagenomic sequencing, revealing many novel viruses in crops, wild plants and microbial hosts. Plant viromes often dominated by RNA viruses can influence disease emergence, host resistance and stress tolerance. At the same time, synthetic microbiomes (laboratory-designed consortia of beneficial bacteria, fungi and other microbes) are being developed to bolster plant defenses and resilience. This review synthesizes current knowledge on plant-associated viromes and engineered microbiomes, focusing on how they reshape plant disease and pest dynamics in the Anthropocene. We first define key concepts: the plant virome, microbiome and synthetic community and outline the scope of their relevance. We describe methodologies for virome detection (including untargeted sequencing and computational virus discovery) and for designing synthetic communities (from isolation to in planta assembly). We examine ecological and evolutionary consequences: for example, how virus reservoirs in wild flora can spill over into crops, how coevolution under stress may convert viruses into mutualists and how tailored microbial consortia can suppress pathogens or affect insect pests. We then discuss potential risks of horizontal gene transfer, ecological imbalance, public acceptance and the evolving regulatory landscape for engineered microorganisms. Finally, we identify knowledge gaps (uncharacterized viral taxa, multi-kingdom community dynamics, long-term field outcomes) and propose research priorities for integrating virome science and microbiome engineering into sustainable agriculture.